2023
DOI: 10.1007/s12665-023-10807-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ABCD water balance conceptual model using remote sensing data in ungauged watersheds (a case study: Zarandeh, Iran)

Abstract: Water balance is one of the most important issues in water resources management and water consumption planning.ABCD water balance conceptual model is a very suitable simulation tool due to its simplicity, low requirement of input data, and providing various components of the water balance. As the lack of data is always a major challenge in many developing countries, remote sensing technology was used to collect the required data for the Zarandeh subbasin in Neyshabur in the Northeastern Iran. To do so, IMERG p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(21 reference statements)
0
3
1
Order By: Relevance
“…This indicates the satellite product's accurate precipitation estimation and high performance in this particular geographical area. Compared to another study conducted in the province, the BIAS in Qaretikan is lower, ranging from −6 to 3.7 [9]. This suggests that this product provides a more precise estimation of precipitation in this specific area.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…This indicates the satellite product's accurate precipitation estimation and high performance in this particular geographical area. Compared to another study conducted in the province, the BIAS in Qaretikan is lower, ranging from −6 to 3.7 [9]. This suggests that this product provides a more precise estimation of precipitation in this specific area.…”
Section: Resultscontrasting
confidence: 55%
“…Their findings indicated that both datasets were able to accurately represent the climatological patterns of precipitation and maximum and minimum temperatures, with ERA5-Land exhibiting slightly superior performance. Baseri et al [9] utilized IMERG and ERA5 data for water balance modeling, demonstrating the high performance of these products in their study. Evaluation of GLEAM in multiple regions has shown a strong correlation with observational data and low root-mean-square error (RMSE) [29][30][31].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The overall deviation of the water quantities derived from the ABCD model from the observations at the BZA and SD hydrological stations is positive, which suggests that the model slightly overestimates the actual observed values of the mean hydrological processes. The NSE is more than 0.8, and the Pbias is less than 10%, which indicates that the ABCD model is a good fit and can be used for hydrological simulation in JRB [45].…”
Section: Streamflow Simulation Using Abcd Modelmentioning
confidence: 96%
“…In efforts to improve hydrologic models and bring reliable flow prediction in ungauged watersheds as a parallel method to calibration, regional analysis, which transfers certain common information from one catchment to another within a specified homogeneous geographic area, has been utilized extensively [21,26], and Important progress is being made to regionalize continuous simulation using parsimonious rainfall-runoff models [25,27]. However, since lack of data continues to be the major issue in many developing nations, simple conceptual water balance models such as ABCD using satellite products as data sources for meteorological variables are suitable tools for simulation [28].…”
Section: Introductionmentioning
confidence: 99%